Republic of Madagascar : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses key findings of the Financial System Stability Assessment concerning Madagascar. The analysis reveals that the Madagascar's banking sector is exposed to significant risks, though it has certain buffers, such as high profitability and a stable deposit base. Currently the economy is recovering, and enjoys the prospect of resumption in inflows of foreign aid and investment; inflation is coming down and the balance of payments has strengthened. Banking supervision is not yet able to proactively detect and address emerging risks; doing so will require additional resources and political will. Efforts are also needed to promote financial deepening and inclusion, consistent with the maintenance of stability and consumer protection.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet